Coordinated Control of a Wind-Methanol-Fuel Cell System with Hydrogen Storage - Tiejiang Yuan; Qingxi Duan; Xiangping Chen; Xufeng Yuan; Wenping Cao; Juan Hu; Quanmin Zhu (Energies, 2017)
This paper presents a wind-methanol-fuel cell system with hydrogen storage. It can manage various energy flow to provide stable wind power supply, produce constant methanol, and reduce CO2 emissions. Firstly, this study establishes the theoretical basis and formulation algorithms. And then, computational experiments are developed with MATLAB/Simulink (R2016a, MathWorks, Natick, MA, USA). Real data are used to fit the developed models in the study. From the test results, the developed system can generate maximum electricity whilst maintaining a stable production of methanol with the aid of a hybrid energy storage system (HESS). A sophisticated control scheme is also developed to coordinate these actions to achieve satisfactory system performance.